1979
DOI: 10.1021/jo01319a039
|View full text |Cite
|
Sign up to set email alerts
|

N-Acylcarbamates as intermediates in synthetic approaches to a bicyclic trimethylene-bridged 2,4-oxazolidinedione and hydantoin

Abstract: CH:!=CKlR* (R1 = COOCzHa, R:! = HI, 140-88-5: CHz=CRlR2 (R1 = COOCH3, Rz = CH3), 80-62-6; CH2ZCRiR2 (Ri = CN, R? = HI, 107-13-1; CH2=CR1R2 (R1= C & , , Re = H ) , 100-42-5; C H Z~C R~R~ (R1 = CsHj. RP = CH3), 98-83.9; C H~E C R I R~ (R1 = CsHj. R:! = CsHs). 530-48-3; CHz=CRiRp (R1 = H ) , 827-54-3; CH2=CRlR:! (R1 = CsHj, Rz = COOCZHj), 22286-82-4; CH2=CR1Ri iR1 = CsHj, RZ = COCH3), 32123-84-5: CHe=CRiRz (R1 = CsHh, R2 = COCzHa), 66551-91-5; CHz=CR1R:! = a-naphthyl, R:! = H). ,826-74-4: CH2=CR1R2 (R1= &naphthyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1979
1979
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Moreover, Smissman found that structures of bridged imides reported in the literature by other groups were incorrect (Scheme 88). 388,389 Inspired by Smissman's work, 390 in 1984, Brouillette accomplished the synthesis of bridged 2,4-oxazolinediones containing [4.2.1] and [5.2.1] ring systems using acylation of α-hydroxy lactams with aryl chloroformate as a key step (Scheme 89). 391 Thus, the reaction of lactams 330 with 4nitrophenyl chloroformate in refluxing toluene provided bridged oxazolinediones 331b−c in 44−90% yields.…”
Section: Heteroatom-containing Derivatives Of Bridged Lactamsmentioning
confidence: 99%
“…Moreover, Smissman found that structures of bridged imides reported in the literature by other groups were incorrect (Scheme 88). 388,389 Inspired by Smissman's work, 390 in 1984, Brouillette accomplished the synthesis of bridged 2,4-oxazolinediones containing [4.2.1] and [5.2.1] ring systems using acylation of α-hydroxy lactams with aryl chloroformate as a key step (Scheme 89). 391 Thus, the reaction of lactams 330 with 4nitrophenyl chloroformate in refluxing toluene provided bridged oxazolinediones 331b−c in 44−90% yields.…”
Section: Heteroatom-containing Derivatives Of Bridged Lactamsmentioning
confidence: 99%
“…1, 93350-08-4; 2, 93350-09-5; 3, 92288-54-5; 4, 68475-20-7; 5, 65379-06-8; 6, 87532-76-1; 7, 87532-77-2; 8, 87532-78-3; 9, 51129-01-2; 10, 93350-14-2; 11, 93350-13-1. Synthesis of (Aryloxy)alkylamines. 2. Novel Imidazo-fused Heterocycles with Calcium Channel Blocking and Local Anesthetic Activity1 Pauline J. Sanfilippo,* Maud Urbanski, Jeffery B.…”
Section: Ns23866)mentioning
confidence: 99%
“…12 The and 13C NMR assignments for 2 are presented in Table I and are consistent with the assigned structure. The reaction of 2 with Br2 and CH3OH according to the procedure of Smissman6 produced a crystalline product that was identical in every respect (mp, IR, and NMR in CF3C02H-d1) to that reported as 3. Furthermore, the electron-impact mass spectrum gave the anticipated molecular ion at m/e 356 and confirmed the presence of one bromine.…”
mentioning
confidence: 90%